Peran Teori Humanistik Carl Rogers dalam Aktualisasi Diri Peserta Didik Berkebutuhan Khusus di Tengah Krisis Mental - Lu’luil Munawiroh; Qorri Aina Nadra; Vina Tri Apriliani; Estiningsih; Ali Masyhuri; Labibah Azizatus Shalehah Abdul Khaoliq; Bagus Mahardika (PT. Nawa Edukasi Nusantara, 2026)
This study aims to analyze the application of Carl Rogers' humanistic learning theory in encouraging self-actualization of Students with Special Needs (PDBK) amidst the challenges of the mental health crisis. The main focus of the study was deaf students at the Marsudi Putra 2 Pandak Special Needs School in Bantul, D.I. Yogyakarta. This study used a descriptive qualitative method with data collection techniques through interviews, observation, and documentation. The results showed that the implementation of Rogers' three pillars—unconditional positive regard, empathy, and congruence—served as the foundation for resilience for students. Teachers at the Marsudi Putra 2 Pandak Special Needs School adopted the role of facilitators and parental figures to create a safe space that was able to minimize the gap between students' real and ideal selves. The instructional strategies used included the Maternal Reflective Method (MMR), visual methods, lip reading, and total communication aimed at enriching vocabulary and training students' emotional stability. Despite facing challenges such as student learning boredom and complex verbal communication barriers, this humanistic approach proved effective in building a positive self-concept. Integrated social support between teachers, parents, and peers is a crucial factor in directing students' psychological energies toward self-actualization and the development of fully functioning individuals.